Patronage factors that influence people to choose Takaful Ikhlas (Ikhlas Consultant & Services) / Nurulhasanah Rebuyan - Rebuyan, Nurulhasanah (2010)
Despite the thriving growth of the industry, Takaful just captures a small portion of market share of the insurance industry. Thus, there is a need for IKHLAS Consultant & Services (Takaful Ikhlas) for determine what the factors that are considered as important for the customers to adopt their product especially among Muslim. There is also a need for IKHLAS Consultant & Services (Takaful Ikhlas) to capture more muslim to buy their product. For the purpose of the study, exploratory research developed in order to identify the patronage factors that influence people to choose Takaful products, to identify the products/services adopted by customers of Takaful, and to analyze the differences of patronage factors between muslim and non-muslim customers on Takaful products. Simple random sampling has been utilized with 110 respondents of the sample size. Selfadministered questionnaire was used as the survey instrument. By using the analysis generated by Statistical Package for the Social Science (SPSS), results are analyzed. This research found that, convenience, reputation and service provision are the patronage factors that influence people to choose Takaful products. The researchers also found that majority of respondents are Muslim with 90.9% ad frequency of 100 respondents, while non-muslim with 9.1%. Thus, it proved that, for Muslim, the elements of gharar, mysir and riba’ are important in making their decision to choose their operator. In terms of product adopted by customers, most of the respondents choose Ikhlas Saving Takaful.